UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR RUMPUT LAUT KE TIONGKOK PADA MASA PANDEMI COVID-19 - Dilla, Octa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This article aims to research and understand Indonesia's efforts to increase seaweed exports which experienced a decline during the Covid-19 pandemic to China in 2020-2022. The main focus of this article is Indonesia's role in increasing seaweed exports to China during the pandemic. This article uses a liberalism perspective at the nation-state level of analysis. This paper also uses international trade theory. The method used in this paper is qualitative research and is explanatory in nature by searching several literatures such as books, journals, internet articles, as well as various sources combined and used to complete the needs of this paper. The result of this article is that Indonesia is taking strategic steps as a form of effort to increase seaweed exports to China during the Covid-19 pandemic. There are efforts being made, such as a policy to increase exports through the minister of finance, so that exports can continue during the Covid-19 pandemic. By improving the quality and safety of seaweed and making it free from Covid-19 contamination, Indonesia is making efforts to issue a regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesian 7/PERMEN- KP/2019 concerning Requirements and Procedures for Controlling Certificates for Good Fisheries Handling, through a publishing service SKP (Certificate of Management Feasibility), Indonesian also provides SNI training, seaweed tissue culture seed training, seaweed management training through the foreign exchange village program and makes swab tests for products that will be exported to China to detect Covid-19 virus contamination in order to comply with new regulations. made by China regarding the condition for exports to be free from Covid-19. Indonesian seeks international cooperation with China through an agreement to strengthen maritime cooperation. Apart from that, Indonesia is also trying to take advantage of international forums such as ASEAN Plus Three and making efforts to promote seaweed at international virtual seafood shows during the Covid-19 pandemic.and tell to buyers that indonesian seaweed free contamination Covid-19. Keywords: seaweed, China, and Covid-19